Comparative genetic, clinical features, and 5-years outcomes for dilated vs noncompaction cardiomyopathy. (25th November 2020) - Vaikhanskaya, T; Sivitskaya, L.N; Danilenko, N.G; Liaudanski, A.D; Davydenko, O.G
Abstract: : Non-compaction cardiomyopathy (NCCM) and dilated cardiomyopathy (DCM) are associated with high risk of adverse cardiovascular events. Objective: To investigate the genetic architecture of NCCM and DCM with comparing the incidence rate of NCCM/DCM related cardiovascular events. Method: The study enrolled 120 unrelated pts with NCCM (n=60; age 38.5±13.8 years; 33/55% male; LVEF 42.1±12.9%) and DCM (n=60; age 40.5±13.5 years; 37/61.7% male; LVEF 30.5±11.1%). Diagnosis of NCCM was confirmed by any three accepted criteria as Echo (Jenni/Stöllberger) and MRI (Petersen/Jacquier) with supporting by clinical evidence (family history, neuromuscular disorders, abnormal ECG, arrhythmia, heart failure or thromboembolism). All pts were examined by ECG, HM, Echo, and MRI. Genetic testing was performed by NGS (174 genes) with Sanger verification. The composite end point was accepted as a major adverse cardiac event (MACE) during follow-up: SCD, HF death, LVAD, HTx, successful resuscitation, sustained VT/VF or appropriate ICD/CRT-D shock. Clinical, genetic data, and MACE during a median follow-up of 5.1 years were compared. Results: Sarcomere gene (SG) variants (TTNtv, MYBPC3, and MYH7) were the most common pathogenic mutations (47.4%) found in gene-positive NCCM (n=33/55% pts). In general, a similar gene structure (SG – 44.4% vs 47.4%; ion channel protein genes – 25.9% vs 18.2%) was detected for genetic DCM (n=27/45% pts) except for LMNA gene (29.6% vs 6.06%, χ 2 =4, 6; p<0.05). Risk of systolic dysfunction (LVEF<49%) was high for NCCM carriers and higher for multiple mutations (Cochran test: OR=38; 95% CI 4.74–305; p=0.0001) and association of gene positivity with a composite end point was determined at the level of prognostic significance (McNemar's test χ 2 =22.9; p=0.0001). NCCM patients had a similar MACE risk compared with DCM pts (OR 0.93; 95% CI 0.45–1.92). The incidence rates of all-cause mortality, stroke, HTx, VT/VF, and cardiac device implantation was comparable in DCM vs NCCM groups (Fig.A). As a result of multiple regression analysis, MACE risk models were constructed with step-by-step inclusion: similar common predictors for NCCM et DCM such as low LVEF (β=−0.37 vs β=−0.32), myocardial fibrosis (nLGE: β=0.19 vs β=0.23), width QRS (β=0.17 vs β=0.21), and a strong predictor for NCCM only - the gene positivity (β=0.85; p=0.0001). Kaplan-Meier analysis confirmed this (Fig. B, C). So, amazing fact revealed for NCCM such as systolic dysfunction (but not extent/number trabeculation or NC/C) and disease-causing gene mutations (β=0.85) that were associated with high MACE risk (R=0.90; R 2 =0.81; F(5.41)=34.8; p<0.00001). Conclusions: NCCM pts had a similar cardiovascular risk and mainly genetic spectrum when compared with DCM pts. The unifying MACE predictor was LV dysfunction for both groups. However, gene positivity was associated with adverse outcomes for NCCM pts only (without detailed analysis the specific/localization causing genetic variants). Funding Acknowledgement: Type of funding source: None